Schistosoma japonicum MiRNA-7-5p Inhibits the Growth and Migration of Hepatoma Cells via Cross-Species Regulation of S-Phase Kinase-Associated Protein 2 - Hu, Chao; Zhu, Shanli; Wang, Jing; Lin, Yu; Ma, Li; Zhu, Liufang; Jiang, Pengyue; Li, Zhengli; Pan, Weiqing (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) play important roles in human diseases, such as cancer. Human miRNA-7-5p is a tumor suppressor miRNA that inhibits tumor growth by regulating multiple oncogenic signal pathways. Recently, studies revealed that plant miRNAs could regulate mammalian gene expression in a cross-kingdom manner. Schistosoma japonicum miRNA-7-5p (designated as sja-miR-7-5p) is conserved between the parasites and mammals. Thus, we investigated whether sja-miR-7-5p has similar antitumor activity to its mammalian counterpart. We first showed that sja-miR-7-5p was detected in host hepatocytes during Schistosoma japonicum infection. The sja-miR-7-5p mimics significantly inhibited the growth, migration, and colony formation of mouse and human hepatoma cell lines in vitro, and induced G1/G0 cell cycle arrest. In a xenograft animal model, the tumor volume and weight were significantly reduced in mice inoculated with hepatoma cells transfected with sja-miR-7-5p mimics compared with those transfected with NC miRNAs. Furthermore, the antitumor activity of sja-miR-7-5p was suggested by cross-species downregulation of the S-phase kinase-associated protein 2 gene in the host. Thus, sja-miR-7-5p is translocated into hepatocytes and exerts its anti-cancer activities in mammals, implying that sja-miR-7-5p might strengthen host resistance to hepatocellular carcinoma during schistosome infection.